Evaluation of synthesis characterization and simulation study of magnetic nanoparticles for ammonia synthesis in MIM - Irfan, M. (American Institute of Physics Inc., 2016)
It is generally understood that magnetic energy is much smaller than thermal energy which dominates the chemical equilibrium. Magnetic nanoparticles (NiO) as catalyst were synthesized by chemical reduction routes following micro emulsion method having an average size of 239 nm and 207.2 nm followed by FESEM and TEM analysis respectively. EDX analysis of nanoparticles (NPs) with 90.80 weight Ni, 9.20 weight O2 and 72.90 atomic Ni, 27.10 atomic O2 falls it into the category of formation of nickel and oxide NPs. TEM for parallel Ni EELs vs intensity is 840.0 eV to 860.0 eV and 70 to 80 respectively. TEM diffraction and fringe spacing analysis of NPs reveals the details about diffraction planes as (200), (311), (400) and lattice parameter 4.136 nm respectively. Both RAMAN spectroscopy and FTIR spectroscopy analysis of NPs elaborate the consistency between peak intensity and RAMAN shift (cm-1) as 318.74 cm-1, 522.78 cm-1, 620.28 cm-1 and 450 cm-1, 515.84 cm-1and 720.08 cm-1 respectively. The saturation magnetization (Ms) of NiO NPs was measured to be 32.524 emu/g by VSM for a specific mass of 14.1x10-3 g. Simulation study based on DFT in term of catalytic effect related to sorbents and sorbates atomistic, thermodynamic and quantum mechanical interactions including adsorption is illustrated in this article using first principal DFT simulation study. The average total energy, average total adsorption energy, average adsorption energy of H2, and N2 over NiO (111) surface are reported as 4.414 kcal/mol, 4.4145 kcal/mol, -1.671 kcal/mol, and 0.869 kcal/mol respectively. Whereas, isosteric heats of adsorption energies for H2, N2 over NiO (111) cleaved surface were calculated to 1.617kcal/mol, and -0.881 kcal/mol respectively. Ammonia synthesis carried out by MIM and peaks were detected by FTIR and yield was quantified by Kjeldahl method in few thousands Î¼mole gcat-1 h-1. Â© 2016 Author(s).